2005
DOI: 10.1002/pssb.200541143
|View full text |Cite
|
Sign up to set email alerts
|

A fast reflectance anisotropy spectrometer for in situ growth monitoring

Abstract: We report on an optical multichannel RAS (Reflectance Anisotropy Spectroscopy) setup capable of measuring at multiple photon energies simultaneously in the spectral range between 1.4 and 5.0 eV at a temporal resolution of up to 30 ms. The setup is specifically designed for time-resolved studies of surface processes (e.g. epitaxial growth). Its accuracy was evaluated on static surfaces by comparison with RAS spectra acquired using a conventional scanning RAS setup. The performance was demonstrated by studying 2… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
16
0

Year Published

2007
2007
2019
2019

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 17 publications
(16 citation statements)
references
References 15 publications
(18 reference statements)
0
16
0
Order By: Relevance
“…Alternatively, RA oscillations may be due to periodic changes in surface reconstruction during layer-by-layergrowth, as suggested in [5]. At the end, however, RA oscillations would be the consequence of a periodic modulation of the surface strain, as it is known that the GaAs RA spectrum around E 1 and E 1 + ∆ 1 energies is dominated by a component associated to the surface orthorhombic strain, that is due in turn to surface reconstruction [14].…”
Section: Resultsmentioning
confidence: 94%
See 1 more Smart Citation
“…Alternatively, RA oscillations may be due to periodic changes in surface reconstruction during layer-by-layergrowth, as suggested in [5]. At the end, however, RA oscillations would be the consequence of a periodic modulation of the surface strain, as it is known that the GaAs RA spectrum around E 1 and E 1 + ∆ 1 energies is dominated by a component associated to the surface orthorhombic strain, that is due in turn to surface reconstruction [14].…”
Section: Resultsmentioning
confidence: 94%
“…On the other hand, we note that the strained island mechanism for RA oscillations predicts the same attenuation time constant as that of RHEED oscillations, as such mechanism is as well associated to surface roughness. Thus, taking into account the fact that RA and RHEED oscillations do display different attenuation time constants, it is suggested that RA oscillations are more likely associated to the periodic modulation of the surface atomic structure as the surface shifts from Ga-rich to Asrich condition [2,5].…”
Section: Resultsmentioning
confidence: 97%
“…These oscillations occur most pronounced for GaAs but have been observed for InP, too. We use a multichannel RAS setup to measure the RAS signal at multiple wavelengths simultaneously [9]. Fig.…”
Section: Resultsmentioning
confidence: 99%
“…The group V precursors were arsine ðAsH 3 Þ and phosphine ðPH 3 Þ, the group III precursors were trimethylgallium (TMGa), triethylgallium (TEGa), and trimethylindium (TMIn silane ðSiH 4 Þ and a dimethylzinc-adduct (DMZn) were used as dopant sources. A multichannel RAS setup was used to record RAS transients at multiple wavelengths simultaneously, together with a conventional RAS system [9]. The free carrier concentration of the layers was analyzed by C-V-profiling.…”
Section: Methodsmentioning
confidence: 99%
“…real time. Instruments with multi-channel detection have been developed that allow a complete spectrum from 1.4 to 3.2 eV to be gathered in 0.1 s [44], while other instruments have been optimized for in situ monitoring of epitaxial growth [45]. RAS is in routine use for monitoring III-V and II-VI semiconductor growth and, recently, it has been shown that growth monitoring can be extended to organic molecular beam epitaxy [46,47].…”
Section: Instrumentationmentioning
confidence: 99%